2018
DOI: 10.1177/2047487318816387
|View full text |Cite
|
Sign up to set email alerts
|

Impact of acetylsalicylic acid on primary prevention of cardiovascular diseases: A meta-analysis of randomized trials

Abstract: Numerous studies have investigated use of acetylsalicylic acid (ASA) for prevention of cardiovascular deaths. The vast majority of the work in this area has focused on secondary prevention. However, underuse of ASA still remains a major issue. Fewer studies have investigated the impact of ASA on primary prevention of cardiovascular death. A meta-analysis of individual participant data from six randomized studies, published in 2009, showed decrease in serious vascular events but at the cost of causing increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…This review was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Protocols 2015 statement ( 24 , 25 ).…”
Section: Methodsmentioning
confidence: 99%
“…This review was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Protocols 2015 statement ( 24 , 25 ).…”
Section: Methodsmentioning
confidence: 99%
“…e present meta-analysis was performed based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines 2015 statement [15,16] and was registered on PROSPERO (CRD42020163716).…”
Section: Methodsmentioning
confidence: 99%
“…A meta-analysis of individual participant data from six randomised studies, published in 2009, showed that the decrease in vascular events after aspirin therapy is burdened by increased bleeding and haemorrhagic stroke rates. 7 To this topic, still a cause of controversy, the metaanalysis of Upadhaya et al, 8 published in the European Journal of Preventive Cardiology, brings further scientific evidence. This meta-analysis was designed in order to assess the risks and benefits of aspirin for primary prevention of CVD.…”
mentioning
confidence: 99%
“…To this topic, still a cause of controversy, the meta-analysis of Upadhaya et al., 8 published in the European Journal of Preventive Cardiology , brings further scientific evidence. This meta-analysis was designed in order to assess the risks and benefits of aspirin for primary prevention of CVD.…”
mentioning
confidence: 99%